Market Reaction in ASEAN: Identifying Themes, Trend, and Future Agenda Through Bibliometric Analysis - Adam, Mukhtar A; Nurdin, Nurdin; Amiro, Suratno; Sardju, Fitriani; Zainuddin, Zainuddin (Cita konsultindo, 2025)
Abstract This study aims to systematically map and synthesize the intellectual structure, thematic evolution, and future research directions of market reaction research in the ASEAN region using a bibliometric approach. Focusing on the period 2019–2025, this study captures the dynamics of market reaction literature before, during, and after the COVID-19 pandemic, a major global shock that reshaped financial market behavior and scholarly attention. ASEAN provides a unique empirical setting due to its heterogeneous market structures, evolving regulatory environments, and increasing integration into global capital markets. Using data extracted from a comprehensive bibliographic database, this study employs Biblioshiny (Bibliometrix-R) and VOSviewer to analyze publication trends, citation patterns, authorship and institutional networks, journal quartile distribution, and keyword-based thematic structures. The results reveal a substantial growth in market reaction research during the pandemic period, followed by a phase of empirical consolidation. While early studies exhibit higher citation impact and serve as foundational references, more recent publications contribute to thematic expansion with lower citation concentration, reflecting a maturing yet increasingly fragmented research landscape. The thematic analysis identifies a highly concentrated intellectual core centered on event study methodologies, abnormal returns, stock returns, and volatility, with a strong geographical orientation toward emerging and Southeast Asian markets. Overlay and density visualizations further demonstrate that COVID-19-related themes rapidly became dominant and reached saturation, highlighting the shock-driven nature of recent research. Journal analysis indicates that most studies are disseminated through Q2 and Q3 Scopus journals, with limited penetration into Q1 outlets, suggesting strong empirical relevance but uneven theoretical integration